2016
DOI: 10.1175/jcli-d-16-0391.1
|View full text |Cite
|
Sign up to set email alerts
|

Faster Arctic Sea Ice Retreat in CMIP5 than in CMIP3 due to Volcanoes

Abstract: The downward trend in Arctic sea ice extent is one of the most dramatic signals of climate change during recent decades. Comprehensive climate models have struggled to reproduce this, typically simulating a slower rate of sea ice retreat than has been observed. However, this bias has been widely noted to have decreased in models participating in the most recent phase of the Coupled Model Intercomparison Project (CMIP5) compared with the previous generation of models (CMIP3). Here we examine simulations from bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 34 publications
(61 reference statements)
4
32
0
Order By: Relevance
“…These estimates cover the range of findings by Rosenblum and Eisenman (2016) and Screen and Williamson (2017). There is substantial observational uncertainty of Arctic sea ice sensitivity for a given degree of global warming.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…These estimates cover the range of findings by Rosenblum and Eisenman (2016) and Screen and Williamson (2017). There is substantial observational uncertainty of Arctic sea ice sensitivity for a given degree of global warming.…”
Section: Discussionsupporting
confidence: 54%
“…Rosenblum and Eisenman (2016) estimate that the Arctic Ocean loses its summer sea ice once global warming rises above 1 ∘ C relative to the period 1980-1999. For the high-sensitivity observational estimate, we find that sea ice area in September drops below this threshold for about 1.7 ∘ C global warming.…”
Section: Sea Ice Area As a Function Of Global-mean Surface Temperaturementioning
confidence: 99%
“…The cause of this reduction in model bias is analyzed in a companion paper (Rosenblum and Eisenman 2016). The ensemblemean Arctic sea ice trend in CMIP5 is still slower than observed (Stroeve et al 2012;IPCC 2013), but the observations fall within the range of simulations (Figures 1b,e).…”
Section: Introductionmentioning
confidence: 89%
“…The IPCC fifth assessment report shows that the models participating in the Coupled Model Intercomparison Project phase 5 (CMIP5, http://pcmdi3.llnl.gov/esgcet) have a higher performance than those in the Coupled Model Intercomparison Project phase 3 (CMIP3) in their capability of reproducing the long-term trends of sea ice. Rosenblum and Eisenman (2016) found that the inclusion of 5 volcanic activity, rather than improvement of sea ice physics or model resolution, accounts for the priority of the CMIP5 over the CMIP3 in simulating the Arctic sea ice trends. Nevertheless, the CMIP5 model simulation results are far from satisfying, especially in the Antarctic region.…”
Section: Introductionmentioning
confidence: 99%